العلاقات التعاقدية لهيئات الرقابة الشرعية وإدارات التدقيق الشرعي ودورها في تعزيز بيئة الحوكمة الشرعية (نموذج رقابي شرعي مُقترح) (Economic studies journal, 2022)
This research paper deals with the contractual relations of Shariah supervisory boards, and Sharia audit departments and their role in enhancing the Shariah governance environment, by defining the concept of Sharia supervisory system in general and Sharia control and Sharia audit in particular and knowing the forms and objectives of Sharia supervisory boards, as well as defining the importance and tasks of Sharia audit, and reviewing the principles And the objectives of Sharia governance, in order to reach the reality of Sharia, supervisory bodies in Libya, and determine the type of contractual relationships between Sharia supervisory bodies, Sharia audit departments, external Sharia auditors and boards of directors in banks for the purpose of strengthening the Sharia governance environment. The study reached to many findings and recommendations. In addition, lay developing a future Shariah supervisory vision that defines contractual relationships and supports the Sharia governance system within our banks
Keywords: Sharia supervisory system; Sharia supervision; Sharia governance; Sharia audit